Bibliography on underutilized roots and tubers crops - Libreros, D.; International Plant Genetic Resources Institute (2001)
Roots and tubers crops are present in the diet of almost all the world's people, the best known are potato and cassava, both of which are of South American origin but are now widely distributed. There are also several species of roots and tubers which originated from South America and which are still of importance to Andean people, such as yacon, white carrot, mauka, maca, achira, oca, mashua and ulluco. These species are little known to farmers and investigators outside the Andean region, and even to some within the region. They are species that have perhaps not been fully exploited or whose potential has not been fully taken advantage of, possibly because their cultivation is restricted and their use localized. Some of these species have a nutritive value and other characteristics that make them very promising candidates for more extensive use. The results of the relatively limited research that has been carried out on these underutilized species by national and international agricultural research institutions, non-governmental organizations and universities is the starting point for future research. This bibliography is a compilation of such results, reflecting the state of knowledge on diverse research subjects and also what still needs to be done, for example in areas such as entomology and pathology. We hope this bibliography will be a valuable tool for researchers and and other professionals working with Andean roots and tuber crops. Available in electronic format only as a Portable Document Format (PDF) file.